“Don’t Trust Anybody, Not Even Us”: Kafka’s Realism as Anarchist Modernism - Jesse Cohn (Studies in 20th & 21st Century Literature, 2011)
Franz Kafka’s personal interest in and contact with the anarchist movement have been fairly well documented, and many have pointed to affinities between his work and anarchist ideas. At the same time, a growing body of scholarship has documented the influence of anarchist politics on modernist aesthetics per se, primarily in terms of a shared resistance to representation—a project that Kafka appears not to share, or at least one he pursues in a very different way. This essay redescribes the strategies of representation found at work in novels such as The Trial and stories such as “The Refusal” in relation to anarchism, and thereby to contribute to a better understanding both of Kafka’s political engagements and his unique form of narrative realism.
Keywords: Franz Kafka; Kafka; anarchist ideas; anarchy; modernist aesthetics; modernism; The Trial; The Refusal; narrative realism; politics; Der Process; Der Prozess